Effect of orientation of walls on the insulation thickness - Özel, Meral; Pihtili, Kazim (My University, 2007)
In this study, taking into consideration the walls insulated on the outside which is widely used in application, the effect of orientation of walls on the insulation thickness has been numerically investigated from heat gains and losses points of view. The study has been carried for three different insulation materials by using meteorological data of Elazi?, İzmir and Kars having different climatic conditions. Results obtained for summer and winter conditions are presented in the forms of graph. Consequently, it is seen that the insulation applied to east and west facing walls must be thicker than insulation of south facing walls.
Duvar yönünün yalitim kalinli?ina etki?si?
Keywords: Heat gains and losses; Insulation thickness; Orientations of wall